A maturity model for blockchain adoption - Huaiqing Wang; Kun Chen; Dongming Xu (Financial Innovation, 2016)
Background: The rapid development of the blockchain technology and its various applications has rendered it important to understand the guidelines for adopting it. Methods: The comparative analysis method is used to analyze different dimensions of the maturity model, which is mainly based on the commonly used capability maturity model. Results: The blockchain maturity model and its adoption process have been discussed and presented. Conclusions: This study serves as a guide to institutions to make blockchain adoption decisions more systematically.
Keywords: 650; Blockchain; Technology adoption; Maturity model